Comparing postoperative analgesia of bilateral serratus anterior plane block and thoracic paravertebral block for children following the Nuss procedure: protocol for a randomised, double-blind, non-inferiority clinical trial - Yi He; Bin Du; Zhi Li; Mingzhe Xu; Xiaojuan Jiang (BMJ Publishing Group, 2023)
Introduction The Nuss procedure, despite being a minimally invasive surgery, is regarded as one of the most painful surgical procedures in children, and postoperative pain control remains a major clinical issue in this population. Thoracic paravertebral nerve block (TPVB) is reported as excellent pain relief for the Nuss procedure despite its challenging performance and associated adverse effects. Serratus anterior plane block (SAPB) is a simplified and effective method for managing thoracic pain as an alternative to TPVB. However, whether SAPB can provide analgesia comparable with that provided by the TPVB approach in children undergoing the Nuss procedure is unknown.Methods and analysis This will be a prospective, randomised, double-blind, single-centre, non-inferiority trial that will enrol children aged 7-16 years subjected to the Nuss operation for pectus excavatum. In total, 74 paediatric patients will be randomly assigned to either the SAPB or TPVB group after general anaesthesia to receive ultrasound-guided regional nerve blocks (0.25% ropivacaine 2.5 mg/kg). The primary outcome will be the assessment of postoperative pain intensity at predetermined time points. The secondary outcomes will include assessing intraoperative opioid intake, consumption of analgesics within 24 hours postoperatively, time of first use of rescue analgesics, extubation time, perioperative adverse events and plasma ropivacaine concentrations across the block groups. Demographic and clinical characteristics (eg, pectus severity and the number of bars used) of the patients will be recorded. All data will be collected by investigators who are blinded to the treatment.Ethics and dissemination Ethical approval was obtained from the Ethics Committee on Biomedical Research of the West China Hospital of Sichuan University (2021-1275). During the period of the study, all procedures will be conducted following the principles of the Declaration of Helsinki. The results of the trial will be published in a peer-reviewed scientific journal.Trial registration number ChiCTR2200056596.